Psychometric assessment of an instrument evaluating the effects of affective variables on students’ WTC in face-to-face and digital environment - Herri Mulyono; Regitha Saskia; Vista Sulaim Arrummaiza; Gunawan Suryoputro (Cogent Psychology, 2020)
The current study was aimed to translate and examine the psychometric characteristics of the Indonesian version of Lee and Hsieh’s (2019) questionnaire measuring the effects of four affective variables (i.e. self-confidence, L2 anxiety, grit, and motivation) on students’ willingness to communicate in face-to-face (F2F) in both inside and outside classrooms, and in a digital environment. Data were collected from 458 students—269 university students, 102 upper secondary school students, and 87 lower secondary school students. Several statistical analyses (i.e. unidimensionality assessment, reliability analysis, misfit analysis, and differential item functioninganalysis) was performed using Rasch analysis. Findings of the study revealed that seven of eight constructs in the Indonesian version of Lee and Hsieh’s (2019) questionnaire is valid with Indonesian samples, and they preserve the psychometric characteristics of the original scale. Recommendations are offered in reference to the findings.